2019
DOI: 10.3389/fonc.2019.00241
|View full text |Cite
|
Sign up to set email alerts
|

Combined Adjuvant of Poly I:C Improves Antitumor Effects of CAR-T Cells

Abstract: Chimeric antigen receptor modified T cells (CAR-T) therapy is an emerging immunotherapy against malignancies. However, only limited success was obtained in solid tumors. Polyinosinic-polycytidylic acid (poly I:C), ligand of TLR3, mediates innate immune and adaptive immune and shows broad antitumor effect on many types of cancer. In the present study, we combined EGFRvIII-targeted CAR-T cells with poly I:C treatment and evaluated the synergic antitumor effect in vitro and in immunocompete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 37 publications
(43 reference statements)
1
51
0
Order By: Relevance
“…3). It has been observed that myeloid-derived suppressor cells (MDSCs) inhibit human CAR T cell responses in tumors, including the CD19 CAR T cell response in lymphoma [77][78][79]. MDSCs inhibit T cells via seven mechanisms: (1) inhibition of the proliferation and activation of CD4 + and CD8 + T lymphocytes through arginase-1 or nitrogen oxide synthase 2 as well as IDO;…”
Section: Bone Marrow (Bm) Microenvironmentmentioning
confidence: 99%
“…3). It has been observed that myeloid-derived suppressor cells (MDSCs) inhibit human CAR T cell responses in tumors, including the CD19 CAR T cell response in lymphoma [77][78][79]. MDSCs inhibit T cells via seven mechanisms: (1) inhibition of the proliferation and activation of CD4 + and CD8 + T lymphocytes through arginase-1 or nitrogen oxide synthase 2 as well as IDO;…”
Section: Bone Marrow (Bm) Microenvironmentmentioning
confidence: 99%
“…20 Polyinosinic-polycytidylic acid (poly I:C), a ligand of TLR3, improves the antitumor effects of chimeric antigen receptor modified T (CAR-T) cells. 21 Ultimo et al reported that poly(I:C)-conjugated nanoparticles efficiently targeted breast cancer cells due to the dsRNA-TLR3 interaction. 19 Bernardo et al found that retinoic acid and poly(I:C) cotreatment activates TLR3; induces the production of type I IFN autocrine signaling, caspase-8 and caspase-3 activation, as well as tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) signaling; blocks breast cancer cell proliferation; and leads to the apoptosis of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[118][119][120] In line with these observations, Kline et al have recently demonstrated that intraperitoneal injection of polyI:C elicits robust anti-leukemia T cell immunity and considerably prolongs survival of leukemia-bearing mice upon the engagement of CD8α + cDC1s. 121 Several combinatorial regimens have been developed to increase the antineoplastic effects of polyI:C, some of which demonstrated pronounced therapeutic activity in preclinical models of melanoma 122,123 as well as CRC, 124,125 mammary, 124 and squamous carcinoma. 122 In particular, systemic administration of the DC growth factor fms-related receptor tyrosine kinase 3 ligand (FLT3 LG) followed by intratumoral polyI:C injections improved magnitude and duration of response to B-Raf protooncogene, serine/threonine kinase (BRAF) and CD274 (best known as PD-L1) blockade in mouse B16 melanomas, via a mechanism involving cDC1s.…”
Section: Preclinical Advancesmentioning
confidence: 99%
“…In this setting, polyI:C significantly increased the levels of effector cytokines such as IL-2 and IFNγ, as well as the lytic activity of CAR-T cells while reducing the number and function of myeloid-derived suppressor cells (MDSC) in the peripheral blood and spleen. 124 Interestingly, Guinn and colleagues have recently reported that IFNγ synergizes with polyI:C in limiting the growth of mouse B16 melanoma and human UM-SCC1 squamous carcinoma cells in vitro, suggesting yet another mechanism through which polyI:C may mediate antineoplastic effects in vivo. 122 Along similar lines, polyI:C and the microtubular poison paclitaxel 128 have been reported to synergistically inhibit the growth of paclitaxel-resistant human CRC cells in vitro through a pathway that involves enhanced interferon beta 1 (IFNB1) expression downstream of TLR3.…”
Section: Preclinical Advancesmentioning
confidence: 99%